Molecular Characterization of Rice OsLCB2a1 Gene and Functional Analysis of its Role in Insect Resistance - Begum, Mahfuj A.; Shi, Xiao-Xiao; Tan, Ye; Zhou, Wen-Wu; Hannun, Yusuf; Obeid, Lina; Mao, Cungui; Zhu, Zeng-Rong (Frontiers in Plant Science, 2016)
In plants, sphingolipids, such as long-chain bases (LCBs), act as bioactive molecules in stress responses. Until now, it is still not clear if these lipids are involved in biotic stress responses to herbivore. Herein we report that a rice LCB gene, OsLCB2a1 encoding a subunit of serine palmitoyltransferase (SPT), a key enzyme responsible for the de novo biosynthesis of sphingolipids, plays a critical role in plant defense response to the brown planthopper (BPH) attack and that its up-regulation protects plants from herbivore infestation. Transcripts of OsLCB2a1 gene in rice seedlings were increased at 4 h, but decreased at 8–24 h after BPH attack. Sphingolipid measurement profiling revealed that overexpression of OsLCB2a1 in Arabidopsis thaliana increased trihydroxylated LCB phytosphingosine (t18:0) and phytoceramide by 1.7 and 1.3-fold, respectively, compared with that of wild type (WT) plants. Transgenic Arabidopsis plants also showed higher callose and wax deposition in leaves than that of WT. Overexpression of OsLCB2a1 gene in A. thaliana reduced the population size of green peach aphid (Myzus persicae). Moreover, the electrical penetration graph (EPG) results indicated that the aphids encounter resistance factors while reaching for the phloem on the transgenic plants. The defense response genes related to salicylic acid signaling pathway, remained uplgulated in the OsLCB2a1-overexpressing transgenic plants. Our data highlight the key functions of OsLCB2a1 in biotic stress response in plants.